Assessment of the Change in Alignment of Fixed Segment After Adult Spinal Deformity Surgery. Issue 4 (15th February 2018) - Banno, Tomohiro; Hasegawa, Tomohiko; Yamato, Yu; Kobayashi, Sho; Togawa, Daisuke; Yoshida, Go; Yasuda, Tatsuya; Oe, Shin; Mihara, Yuki; Ushirozako, Hiroki; Matsuyama, Yukihiro
Abstract : Study Design: Retrospective study. Objective: To determine the prevalence of loss in fixed segment alignment after surgical correction of adult spinal deformity (ASD) and identify associated risk factors. Summary of Background Data: Altered fixed segment alignment influences global spinal alignment; however, associated risk factors have not been determined. Methods: Data of 63 patients with ASD (55 females; mean age, 68.0 yrs), who underwent corrective fusion from the lower thoracic spine to the pelvis and completed the 2-year follow up, were retrospectively analyzed. Change in alignment early postoperatively and at 2 years postoperatively was evaluated using the fixed segmental angle (FSA) and fixed vertebral angle (FVA). The predictive value of the following parameters was evaluated: age, sex, body mass index (BMI), high grade osteotomy, rod material, screw loosening, spinopelvic parameters [T1 pelvic angle (TPA), sagittal vertical axis (SVA), pelvic tilt (PT), lumbar lordosis (LL), thoracic kyphosis (TK), and proximal junctional kyphosis (PJA), and Oswestry Disability Index (ODI) scores]. Results: Change of 2.4° in FSA and –3.1° in FVA were identified 2 years postoperatively, with higher intrarater and interrater reliability for FSA. Based on minimal detectable change in FSA, patients were classified into two groups: (+) loss (ΔFSA >3°) and (–) loss (ΔFSA ⩽3°). Correction loss occurred in 17 patients; these patients had a greater BMI, higher rate of high-grade osteotomies, commercially pure titanium (CP) rods implanted, screw loosening, higher preoperative and postoperative TPA, and higher TPA, SVA, and PT after 2 years, than patients without correction loss. Conclusion: The loss of sagittal fixed segment alignment was relatively high at 27%. Greater BMI, high-grade osteotomies, CP rod use, and sagittal malalignment were associated with correction loss after ASD surgery. Level of Evidence: 4